Energy conservation in the refrigeration system through improvement of Coefficient of Performance and power consumption reduction using Nanofluids. Issue 1 (31st December 2022) - Jeyakumar, Nagarajan; Uthranarayan, C.; Narayanasamy, Bose
Abstract : The performance of the refrigeration system can be improved by means of employing Nano refrigerants by dispersing Nanoparticles. In the present study, CuO, ZnO and Al2 O3 nanoparticles have been synthesised by chemical method and characterised by means of Scanning Electron Microscopy and Fourier Transfer Infrared Spectroscopy. The effect of Nanofluid refrigerants on the Coefficient of Performance and power consumption have been studied. Improvement in COP was achieved for CuO and Al2 O3 Nano refrigerants such as 12.2% and 3.42% respectively when compared to normal refrigerants at 0.1% with Polyester oil. Reduction in power consumption has been achieved for CuO and Al2 O3 Nano refrigerants such as 1.39% and 0.6% respectively when compared to normal refrigerants at 0.1% with Polyester oil. Effective improvement has been achieved by Nano-refrigerant in Vapour Compression Refrigeration system, which can be attributed to the dispersion property of Nanoparticles which enhances the thermal conductivity and heat transfer coefficient.